Báró Bánffy Dániel, az Erdélyi Párt földművelésügyi minisztere a magyar kormányban 1940 és 1944 között: BARON DÁNIEL BÁNFFY, THE TRANSYLVANIAN PARTY’S MINISTER OF AGRICULTURE IN THE HUNGARIAN GOVERNMENTS BETWEEN 1940 AND 1944 - Murádin, János Kristóf (Közép-Európai Közlemények, 2020)
The study deals with an almost forgotten Hungarian politician from Transylvania, baron Dániel Bánffy, who was Minister of Agriculture in the Hungarian Governments between 30 December 1940 and 21 March 1944. Dániel Bánffy was an aristocrat came from a Hungarian noble family, which had a very important role in the history of Transylvania. He was an expert in forestry and wood processing, with a large experience on economic field. After the Second Vienna Award which turn Northern Transylvania under Hungarian control in 30 August 1940, Bánffy became deputy in the Hungarian Parliament and joined the newly created Transylvanian Party. In the followings, as Minister in the Hungarian Government, he maintained the interests of the Transylvanian Party on the field of economy and agriculture. Dániel Bánffy shortly became one of those Hungarian politicians of the period who did the most for the economic development of Northern Transylvania. Unfortunately, the times of war during his mandate as Minister of Agriculture doesn’t permitted him to realize his purpose. In this way only a part of his great program of development should came to fruition. After 19 March 1944, the German invasion against Hungary, Dániel Bánffy was arrested by Gestapo, being released only in November. In the first years of Communist Regime in Hungary he was also persecuted, being in force residence together with his family. Dániel Bánffy died in 1955. This study tries to bring him back in the collective historical remembrance. The source material of the paper consists of archival data, special books, studies, memoirs, interviews and articles of the contemporary press.